2021
DOI: 10.1186/s13550-021-00783-w
|View full text |Cite
|
Sign up to set email alerts
|

Parameters predicting [18F]PSMA-1007 scan positivity and type and number of detected lesions in patients with biochemical recurrence of prostate cancer

Abstract: Background Detection of the site of recurrence using PSMA-PET/CT is important to guide treatment in patients with biochemical recurrence of prostate cancer (PCa). The aim of this study was to evaluate the positivity rate of [18F]PSMA-1007-PET/CT in patients with biochemically recurrent PCa and identify parameters that predict scan positivity as well as the type and number of detected lesions. This monocentric retrospective study included 137 PCa patients with biochemical recurrence who underwen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 46 publications
4
25
0
2
Order By: Relevance
“…Reviewing titles and abstracts, 83 records were excluded: 70 because not in the field of interest of this review, 7 as reviews, editorials, or letters, and 6 as case reports. Fifteen articles were selected, and their full-text version was retrieved [ 22 36 ]. No additional studies were found screening the references of these articles.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Reviewing titles and abstracts, 83 records were excluded: 70 because not in the field of interest of this review, 7 as reviews, editorials, or letters, and 6 as case reports. Fifteen articles were selected, and their full-text version was retrieved [ 22 36 ]. No additional studies were found screening the references of these articles.…”
Section: Resultsmentioning
confidence: 99%
“…Three articles were excluded from the meta-analysis for possible patient data overlap [ 24 , 28 , 34 ] and two for insufficient data to calculate the DR on a per scan-based analysis [ 32 , 36 ]. Finally, 10 articles were included in the quantitative analysis (meta-analysis) [ 22 , 23 , 25 27 , 29 31 , 33 , 35 ]. Tables 1 – 3 show the characteristics of the selected studies and their main findings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations